Hardware Design Challenges in ECG Sensing Receivers for Implantable Cardiac Monitors: A Technical Analysis - Rajshaker Reddy Kankula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The development of implantable cardiac monitors presents multifaceted challenges in hardware design, particularly for high-accuracy ECG sensing receivers. The design considerations span across analog front-end architectures, signal processing implementations, system integration strategies, power management solutions, and comprehensive validation methodologies. Advanced technologies in mixed-signal integration, biocompatible materials, and machine learning algorithms have enabled significant improvements in ECG signal quality, power efficiency, and device longevity. The integration of sophisticated filtering techniques, adaptive processing algorithms, and robust validation protocols ensures reliable cardiac monitoring while maintaining strict compliance with medical device standards. These advancements are helping contribute to enhanced patient care through improved diagnostic capabilities and device reliability.